Interaksi @Batamliciouz Melalui Instastory Sebagai Perantara Terciptanya Electronic Word Of Mouth - Ananda, Fawnia; Pamungkas, Indra Novianto Adibayu; Melano, Fiqie Lavani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
Influencer phenomenon Profession on Instagram is increasingly popular, especially in the culinary business sector, where each Influencer definitely has unique and different characteristics in communicating a product/brand to create E-WOM. The obstacles that arise come from the Influencer himself regarding how he can form good interactions with the audience so that he can create E-WOM based on Symbolic Interaction Theory with three important concepts Mind, Self, Society while the content created does not contain the Be Remarkable principle regarding Angle Process Creativity. The method used is a descriptive qualitative research method with an interpretive approach. Informant research is based on Exponential Non-Discriminatory Snowball Sampling, where one source provides several references for the researcher to explore until the information and data are deemed sufficient. The results of this research found that @Batamliciouz succeeded in promoting Kembang Ayu Café through InstaStory by combining Mind, Self, Society and the principles of Be Remarkable, Be Relevant, Be Reasonable, Be Repeatable. Even though creative challenges arise, success is achieved by the interactions carried out by @Batamliciouz through conveying clear information (Mind), a positive image (Self), and content that invites Topicality (Society) thus contributing positively to creating Electronic Word of Mouth.